The development of PARP as a successful target for cancer therapy. Issue 2 (1st February 2018) - Ferrara, Roberto; Simionato, Francesca; Ciccarese, Chiara; Grego, Elisabetta; Cingarlini, Sara; Iacovelli, Roberto; Bria, Emilio; Tortora, Giampaolo; Melisi, Davide
ABSTRACT: Introduction : PARP1 and BRCA genes are essential genome caretakers and their interaction has been the first example of synthetic lethality, a genetic concept proposed in the early 20th century, but deeply explored in cancer patients only in the last decade. Areas covered : This review describes PARP1 and BRCA main functions and different roles in genome protection. Furthermore, an overview of the principle mechanisms of action and resistance to PARP inhibitors (PARPi) is presented. This review illustrates the concept of BRCAness, and how this discovery has broadened the routes of PARPi to several different malignancies such as ovarian, breast and prostate cancer. Finally, an insight is provided into the key data of PARPi in these distinctive clinical settings. Expert commentary : PARP inhibition could be a new therapeutic option for a number of tumors in the near future. However, several aspects will be of paramount interest for future investigations, including the molecular bases for PARPi synthetic lethality, the DNA repair independent functions of PARP and BRCA genes, the resistance and biomarkers of response to PARP inhibition, and the mechanisms of interaction between PARPi and antiangiogenic or immunotherapeutic agents.